THE TRANSFIGURATION ERROR IN ROWLING’S HARRY POTTER AND THE CHAMBER OF SECRET - Siegfrieda A.S. Mursita Putri (Lire Journal (Journal of Linguistics and Literature), 2018)
Translator is always given two options in translating literary works. Either they can pick formal orientation, or pick dynamic orientation. Both orientations have different effect for readers. Harry Potter and the Chamber of Secret is one best-selling novel written by J.K. Rowling. Her work in the series is known for the play of words. This paper proposes other version of translation by exposing several sentences taken from the novel.